G537 A quality improvement project to address ineffective neonatal handover in a district general hospital. (27th April 2016) - Thompson, N; Mc Feely, C; Mc Conaghy, L; Leemon, D; Dowling, T; Campbell, E; Kennedy, R; Coyle, C; Anandarajan, M
Abstract : Context: This quality improvement (QI) project has been implemented in a district general hospital. Staff involved are junior and senior paediatric medical staff and nursing staff. Local management were involved to ensure changes were compliant with local hospital policy. Problem: Change in doctors' working hours has led to an increase in the frequency and complexity of handover. Current handover practice is not robust enough to deal with these demands. Poor handover can lead to lost or misinterpreted information, thus compromising patient care. The RCPCH has produced a guideline for 'Good Practice in Handover'. It was identified that neonatal handover in our unit was sub-optimal, resulting in recent incident reporting of errors in antibiotic administration and missed screening. In this QI activity, the aim was to assess baseline handover, and make monthly changes to the process while monitoring improvements. Assessment of problem and analysis of its causes: Surveys were used to assess staff opinion of current handover practice. A baseline audit of handover was performed in August 2015. The standard was based against the RCPCH guideline and an audit proforma was designed from this document. Data was presented to the multidisciplinary team for discussion. Intervention: To drive improvement, a different problem is addressed each month in the handover process. The first action was to standardise start times, update the electronic format and educate staff on the SBAR method of handover and safety briefing. The current PDSA cycle is focusing on minimising interruptions and increasing senior medical staff presence at handover. Study design: The Institute for Healthcare Improvement (IHI) model was used to drive changes, with regular PDSA cycles. After the initial snapshot baseline audit analysis, a monthly action was implemented. A second audit was performed after four weeks, to assess if change had led to improvement. Following this cycle, further key areas were addressed, including location of handover and senior staff presence at handover. These changes were implemented through staff education meetings and poster campaigns. Strategy for change: Changes were implemented through multidisciplinary staff education sessions. Posters were used to raise awareness on the wards. Discussions with key senior members of staff at the end of each PDSA cycle allowed for approval of change. The timetable for change is a two monthly PDSA cycle with several key areas being addressed during each cycle. The project will run over a twelve month period. Measurement of improvement: The effects of each change were measured by a snapshot audit after a two week implementation phase. The audit tool remained the same throughout allowing for direct comparison. Changes made to date have resulted in >80% of handovers following a standardised SBAR format and >40% of handovers including a safety brief from a baseline of 0%. The current cycle is targeting interruptions in handover, and consultant presence at handover. The follow up audit is underway after implementation of these changes. Effects of changes: There have been no serious adverse incidents or incident reports submitted during the study period relating to poor handover. There have been no missed antibiotics or missed screening of infants on the postnatal ward since the start of the study period. A balancing measures that has been addressed is the delay in starting the morning paediatric handover. This has been resolved by limiting morning handover to unwell patients or new admissions only. Lessons learnt: This QI project has highlighted the need to identify a problem and establish baseline data for comparison. The IHI model is effective to drive change. In each PDSA cycle, a small measurable change should be addressed. Staff buy in is essential to drive change, so education of staff should be prioritised. Message for others: This project highlights the importance of effective handover, in order to prevent system errors and improve patient safety.